2014
DOI: 10.1080/02626667.2013.793799
|View full text |Cite
|
Sign up to set email alerts
|

The role of science in setting water resource use limits: case studies from New Zealand

Abstract: Water resource use limits ensure protection of environmental values and define the availability and reliability of water supply for out-of-channel use. We examined how three types of scientific tools (environmental flow setting methods, hydrological analyses for setting total allocations and spatial frameworks) have been used to define limits across jurisdictional regions comprising multiple catchments in New Zealand. We found that recently developed minimum flow and total allocation setting tools are widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Firstly, they are imposed to constrain human-induced alteration of water quality and quantity to levels that are considered sufficient to sustain environmental values. Secondly, they are necessary to ensure that the total availability of water resources and their reliability is quantified and understood (Snelder et al 2013). In order to set effective and transparent limits that meet environmental objectives, managers require biologically relevant guidelines that reflect both lethal and sub-lethal effects, and indicate an appropriate level of protection under the influence of an environmental stressor.…”
Section: Degree Of Impairmentmentioning
confidence: 99%
“…Firstly, they are imposed to constrain human-induced alteration of water quality and quantity to levels that are considered sufficient to sustain environmental values. Secondly, they are necessary to ensure that the total availability of water resources and their reliability is quantified and understood (Snelder et al 2013). In order to set effective and transparent limits that meet environmental objectives, managers require biologically relevant guidelines that reflect both lethal and sub-lethal effects, and indicate an appropriate level of protection under the influence of an environmental stressor.…”
Section: Degree Of Impairmentmentioning
confidence: 99%
“…Zealand must comprise at least a minimum flow (the flow below which no water can be 63 abstracted) and an allocation limit (a limit on the amount of abstraction taken from the 64 resource) (New Zealand Government, 2011; Snelder et al, 2013). 65…”
Section: Introduction 54mentioning
confidence: 99%
“…This has prompted the search for thresholds of hydrological alteration that cause significant ecological change, such as minimum flow determination. Such relationships have been developed in many countries, including Australia (Arthington et al 2014), Japan (Sui et al 2014) and New Zealand (Snelder et al 2014). Richter et al (2012) suggested a precautionary standard of 10% alteration in any flow variable from natural flows to afford a high level of ecological protection in the absence of detailed site-specific data.…”
Section: Flow-ecology Relationshipsmentioning
confidence: 99%
“…Banks and Docker (2014) reported that institutional arrangements for flow releases from dams in the Murray-Darling Basin, Australia, are organized for irrigation and it is difficult to respond to environmental flow needs. Snelder et al (2014) argued that the uptake of scientific tools in New Zealand has enabled improvements in the clarity of water management objectives and the transparency of limits defined by regional water management plans. Even when environmental flows have been implemented, there must be appropriate monitoring and assessment of compliance.…”
Section: Implementing Environmental Flowsmentioning
confidence: 99%